103 Training load and other risk factors for soft tissue injury risk in professional rugby union: a 13 team, 2-season study of 383 injuries. (3rd March 2020) - West, Stephen; Williams, Sean; Cazzola, Dario; Cross, Matthew; Kemp, Simon; Stokes, Keith
Abstract : Background: The risk of injury in professional rugby union is high compared with other sports. Modifiable risk factors such as training load provide an attractive target for risk management. Objective: To explore the influence of training load on soft tissue injury risk, while accounting for other known risk factors. Design: Observational cohort. Setting: Thirteen professional (English Premiership) rugby clubs over two seasons. Patients (or Participants): During two seasons, 433 and 569 players were recruited, resulting in 1002 player seasons from 696 unique players. Interventions (or assessment of risk factors): Training load metrics (session Rating of Perceived Exertion [sRPE]), previous injury, previous concussion, match minutes, age and position. Main outcome measurements: Soft tissue injury hazard (daily risk). Results: Age and position were unclear risk factors for injury. Previous injury, previous concussion, and match minutes showed clear relationships with soft tissue injury. For training load measures, 3-day acute load showed no clear relationship with injury risk, while moderate–high 14-day chronic loads demonstrated a ' likely ' harmful effect on injury risk (Relative Risk: 1.4, 95% CIs:1.1–1.8). Low values of 3:14 day acute:chronic workload ratio (ACWR) demonstrated 'very likely' harmful effects on injury risk (HR: 2.3, 95% CIs:1.1–4.9) while high ACWR values represented an unclear relationship with injury risk. Values in the 75th percentile for ACWR (1.26) represented a ' likely' beneficial reduction in injury risk compared with median values (0.82)(HR: 0.7, 95% CIs:0.4–1.1). Conclusions: Clear associations between injury risk and training load measures (chronic and ACWR loads) were identified, although low ACWR was associated with greater risk, which is different from previous research findings. While this supports the modification of loads to manage injury risk, the use of individual athlete profiling to include other risk factors (e.g., previous injury, previous concussion and match minutes) should also be undertaken to inform risk management decisions in athlete training programmes.